RAD51 and XRCC3 Polymorphisms Are Associated with Increased Risk of Prostate Cancer. (2nd May 2019) - Nowacka-Zawisza, Maria; Raszkiewicz, Agata; Kwasiborski, Tomasz; Forma, Ewa; Bryś, Magdalena; Różański, Waldemar; Krajewska, Wanda M.
Abstract : Genetic polymorphisms in DNA repair genes may affect DNA repair efficiency and may contribute to the risk of developing cancer. The aim of our study was to investigate single nucleotide polymorphisms (SNPs) in RAD51 (rs2619679, rs2928140, and rs5030789) and XRCC3 (rs1799796) involved in DNA double-strand break repair and their relationship to prostate cancer. The study group included 99 men diagnosed with prostate cancer and 205 cancer-free controls. SNP genotyping was performed using the PCR-RFLP method. A significant association was detected between RAD51 rs5030789 polymorphism and XRCC3 rs1799796 polymorphism and an increased risk of prostate cancer. Our results indicate that RAD51 and XRCC3 polymorphism may contribute to prostate cancer.